Rapid detection of Gram-negative bacteriuria by Limulus amoebocyte lysate assay. - Nachum, R (1981)
The Limulus amoebocyte lysate (LAL) test was evaluated for rapid detection of gram-negative bacteriuria in an adult patient population. Time to gelation of a standard LAL preparation was used as a measure of significant (greater than 10(5) bacteria per ml) gram-negative bacteriuria, and the results of 190 LAL assays were compared with quantitative urine cultures. Initially, 33 of 36 urine specimens containing greater than 10(5) gram-negative bacteria per ml were detected by LAL assay. The three false-negative LAL tests were the result of urine pH levels below the pH minimum for LAL gelation; neutralization of these urine specimens resulted in positive LAL assays and 100% correlation with culture results. All 36 bacteriuric urine specimens were LAL positive within 15 min, with the majority of assays (86.1%) being positive after only 10 min of incubation at 37 degrees C. These data compared favorably with gelation times of 15 min when 1 X 10(5) to 2 X 10(5) gram-negative bacteria per ml were added to sterile urine. Two urine samples obtained from male patients with culture-proven gonococcal urethritis yielded positive LAL assays. The LAL assay was shown to correctly differentiate 96.2% of urine specimens as containing less than 10(5) or greater than 10(5) gram-negative bacteria per ml. The results of this study have shown that the LAL test can be used as a rapid, simple, and reliable screening procedure for the diagnosis of clinically significant gram-negative bacteriuria.